Pengembangan Sistem Informasi Manajemen Kepegawaian Berbasis Web dan Mobile pada PT Anugrah Salman Medika - Afina Dwi Saputri; Anita Fira Waluyo (STMIK Banjarbaru, 2025)
This study is motivated by the fragmented implementation of employee administrative processes, such as attendance, leave submission, and payroll management, which leads to low efficiency and potential data inconsistency. This study focuses on the development of an integrated web and mobile based employee information system to improve the effectiveness of personnel data management. The Waterfall model is applied in the system development process, consisting of requirements analysis, system design, implementation, and testing as the application development stages. The developed system integrates geolocation-based attendance, digital leave submission and approval, and digital payroll slips in PDF format. System testing was conducted using a black box approach to examine whether system functions align with user requirements. The testing results indicate that the main system features operate properly and have the potential to improve data management efficiency, information accuracy, and administrative transparency within the organization.Keywords: Management information system; Location-based attendance; Employee leave; Digital payroll slip; Web and mobile application AbstrakPenelitian ini dilatarbelakangi oleh masih terpisahnya proses administrasi kepegawaian, seperti absensi, pengajuan cuti, dan penggajian, yang menyebabkan rendahnya efisiensi dan potensi ketidaksesuaian data. Fokus penelitian ini adalah pengembangan sistem informasi kepegawaian terintegrasi berbasis web dan mobile sebagai upaya meningkatkan efektivitas pengelolaan data kepegawaian. Model Waterfall digunakan dalam pengembangan sistem dengan tahapan analisis kebutuhan, perancangan sistem, implementasi, dan pengujian sebagai alur pengembangan aplikasi. Sistem yang dikembangkan mengintegrasikan fitur absensi berbasis geolocation, pengajuan dan persetujuan cuti secara digital, serta penyajian slip gaji digital dalam format PDF. Pengujian terhadap sistem dilakukan dengan pendekatan black box guna memeriksa kesesuaian fungsi sistem terhadap kebutuhan pengguna. Berdasarkan hasil pengujian tersebut, fitur-fitur utama pada sistem dapat berjalan dengan baik dan berpotensi memberikan peningkatan pada efisiensi pengelolaan data, ketepatan informasi, serta keterbukaan proses administrasi kepegawaian di perusahaan.